DETERMINATION OF DRYING BEHAVIOUR IN INDUSTRIAL TYPE CONVECTIONAL DRYER AND MATHEMATICAL MODELLING - Akan, Ahmet Erhan; Ozkan, Derya Burcu (VINCA INST NUCLEAR SCI, 2020)
In this study, the performance of a stenter (ram machine) that enables the drying of textile products with hot air is theoretically modelled with a diffusion model derived from Fick's second law. The experimental study was conducted in a 10 chamber stenter with three different drying temperatures (110-130-150 degrees C) and three different fabric speeds (10-20-30 m per minute.) by using a fabric consisting of 95% cotton + 5% lycra. The drying behaviour of the dryer was determined by utilizing the data obtained from the studies. With the help of the utilized model, the values of diffusion coefficients and activation energies were obtained, the conformity of data between the model and the experimental studies were compared by using regression analysis, it was observed that the R-2 value varied between 0.9812 and 0.9961.
Keywords: drying; mathematical modelling; stenter; diffusion model; heat and mass transfer; MASS-TRANSFER; DIFFUSION; Thermodynamics